1999
DOI: 10.1103/physrevlett.83.3872
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a Surface-Roughness Spectrum Caused by Stress in Nanometer-Scale Chemical Etching

Abstract: It is reported that a flat free surface of a stressed solid is configurationally unstable under chemical etching and the surface roughness grows with different rates for different spatial frequencies. The theory described in this Letter predicts that with a shallow chemical etching the roughness with spatial frequency below a critical value grows while the roughness of higher frequency decays. The theory was verified via an atomic force microscope experiment with aluminum. This study provides a simple experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 11 publications
(4 reference statements)
1
52
0
Order By: Relevance
“…The strain energy and the chemical energy provide driving forces for dissolution and transport of molecules. The observation is an evolving surface waviness that has been explained theoretically by [3][4][5]. The spectrum of the waves depends on the strain energy of the body surface and the surface energy.…”
Section: Introductionmentioning
confidence: 99%
“…The strain energy and the chemical energy provide driving forces for dissolution and transport of molecules. The observation is an evolving surface waviness that has been explained theoretically by [3][4][5]. The spectrum of the waves depends on the strain energy of the body surface and the surface energy.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in elastic strain energy are commonly assumed not to play a significant role as a driving force for stress-induced solution mass transfer (pressure solution, PS) or for dynamic recrystallisation [e.g., Paterson, 1973;Lehner, 1990]. PS and dynamic recrystallisation are commonly assumed to be driven by differences in grain boundary surface normal stress (rr,•) and/or differences in crystal plastic strain energy, and it can easily be shown that the potential energy drop associated with differences in rr,• or differences in crystal plastic strain is 2 to 3 orders of magnitude larger than the potential energy drop associated with differences in elastic strain energy, at otherwise similar conditions [e.g., Paterson, 1973].…”
Section: Introductionmentioning
confidence: 99%
“…The tendency for a material to change the shape of its reference configuration is represented by the chemical potential, cf. Kim et al (1999):…”
Section: Surface Evolutionmentioning
confidence: 99%
“…With a linearized theory assuming that the amplitude of the height variation of the body surface is small, it leads to symmetric growth in the sense that the growth rate of hills, as an average, is the same as at valleys, and a critical wavelength can be found, cf. (Kim et al 1999;Asaro and Tiller 1972):…”
Section: Surface Evolutionmentioning
confidence: 99%
See 1 more Smart Citation